PSYCHOLOGICAL FACTORS INHIBITING THE COMPLETION OF FINAL PROJECTS: A LITERATURE REVIEW - Uyun, Muhamad; Nurbaiti, Renda Trinanda (Proceeding of International Conference of Islamic Education, 2024)
In higher education, completing a final thesis is a crucial stage that reflects a student's academic achievement. Completing a thesis is often faced with psychological challenges that can affect both the quality and the timing of its completion. This research aimed to explore and analyze the psychological factors that might have hindered students in completing their theses. This study employed a literature review method. The findings indicated that psychological factors such as motivation, anxiety, and self-efficacy could impede the completion of a thesis. Loss of motivation, feelings of anxiety, and a lack of confidence in one's ability to complete the thesis could lead students to procrastinate on their thesis work or even decide not to complete it at all. Additionally, these psychological factors also impacted students' academic abilities. This initial understanding opened the door for further investigation into how psychological intervention strategies could have assisted students in overcoming these obstacles